Pandangan Tuan Guru terhadap Pemimpin Perempuan di Nahdlatul Wathan - Abdurrazak, Abdurrazak; Nadia, Kholimatus (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
This article discusses the teacher’s view of female leaders in the Nahdlatul Wathan organization, an Islamic organization that was once led by a woman, namely HJ. Siti Raihanun Abdul Majid, who is the daughter of the founder of Nahdlatul Wathan, namely TGKH Zainuddin Abdul Majid. The purpose of conducting this study is to obtain estimates or opinions from teachers in West Nusa Tenggara on female leaders in Nahdlatul Wathan. To obtain these answers, the researcher uses gender theory to analyze this issue, then a qualitative research approach with documentation, observation and in-depth interviews. This study found that the decision of the 10th Mukhtamar in Praya, Central Lombok gave rise to female leaders in NW who became the pros and cons between the to camps who both used the Syafi’i Madzhab with the teachings of Ahlussunah Waljama’ah. However, because of differences in interpreting whether or not women are allowed to become leaders in the nusyuz case. This difference in motivated by differences in arguments, understanding of texts, methods of reasoning and ‘illat law due to changes in time, place, and differences in political attitudes and orientations in supporting one faction in NW. the issue of whether or not a woman can become a leader depends on her ability to lead and be accepted by many people, not based on her gender